Multiple nymphoid reproductives in the nests of the neotropical termite, Armitermes euamignathus (Isoptera, Termitidae, Nasutitermitinae) - Costa-Leonardo, Ana Maria; Barsotti, Raquel Cristina; Soares, Helena Xavier [UNESP] (My University, 1996)
Armitermes euamignathus Silvestri (Termitidae, Nasutitermitinae) is a mound building termite that is common in Brazilian regions of the Cerrado vegetation. Multiple neotenic reproductives were found in three isolated nests of these species localized in other secondary habitats different from Cerrado vegetation. The number of second form queens was always higher than the number of secondary males. In two of these nests, the primary king was present along with the second form reproductives. Eggs and brood were found in the three nests but mature alates were present in only one. Multiple neotenic reproductives were never found in the studied Cerrado region where the nests contained only the primary pair. A study of oviposition rate between primary queens and nymphoid reproductives showed an increased number of eggs in the colony headed by neotenic reproductives.